2
$\begingroup$

I am trying to solve the summation

$$ \sum_{n=3}^{\infty} \frac{1}{2^n} \sum_{i=3}^{n} \left\lceil\frac{i-2}{2}\right\rceil $$

I will list some of the simplifications that I've found so far, and then get around to asking my question. Please feel free to point out any logical errors that I have (in all likelihood) made.

$$ \sum_{n=3}^{\infty} \frac{1}{2^n} \sum_{i=1}^{n-2} \left\lceil\frac{i}{2}\right\rceil $$

$$ \sum_{n=3}^{\infty} \frac{1}{2^n} \left(\sum_{i=1}^{\left\lceil\frac{n-2}{2}\right\rceil} i+ \sum_{i=1}^{\left\lfloor\frac{n-2}{2}\right\rfloor} i\right) $$

Since the upper bound in both of the inner summations will be an integer, I have:

$$ \sum_{n=3}^{\infty} \frac{1}{2^n} \left(\frac{\left\lceil\frac{n-2}{2}\right\rceil\left(\left\lceil\frac{n-2}{2}\right\rceil + 1\right)}{2}+\frac{\left\lfloor\frac{n-2}{2}\right\rfloor\left(\left\lfloor\frac{n-2}{2}\right\rfloor + 1\right)}{2}\right) $$

How do I simplify a floor times a floor and a ceiling times a ceiling algebraically?

I'm thinking that the identity

$$ n = \left\lceil\frac{n}{2}\right\rceil + \left\lfloor\frac{n}{2}\right\rfloor $$

might come in handy, but I have very little experience manipulating floors and ceilings algebraically. Let me be clear: I'm not looking for an answer to the summation, just guidance in simplifying this current step.

$\endgroup$
  • $\begingroup$ Did you look at the Wikipedia article Floor and Ceiling Functions. I found some interesting properties there for some other problem. $\endgroup$ – mvw Jun 25 '14 at 14:48
  • 3
    $\begingroup$ Do you really mean what you wrote, or should that be $\lceil \dfrac{i-2}{2}\rceil$ instead of $\lceil \dfrac{n-2}{2}\rceil$? $\endgroup$ – Robert Israel Jun 25 '14 at 14:50
  • $\begingroup$ Should that be $$\sum_{n=3}^{\infty} \frac{1}{2^n} \sum_{i=3}^{n} \left\lceil\frac{i-2}{2}\right\rceil?$$ Otherwise the $i$ isn't really doing anything, and you can quickly simplify that inner sum. $\endgroup$ – Dustan Levenstein Jun 25 '14 at 14:51
  • 2
    $\begingroup$ If so, get rid of the $\lceil \rceil$ by splitting into the two cases $i$ even and $i$ odd. $\endgroup$ – Robert Israel Jun 25 '14 at 14:52
  • $\begingroup$ Thanks, fixed the mistake, I did mean $\left\lceil\frac{i-2}{2}\right\rceil$. $\endgroup$ – Jon Poler Jun 25 '14 at 15:11
1
$\begingroup$

\begin{align*}S&=\sum_{n=3}^\infty\frac{1}{2^n}\sum_{i=3}^n\left\lceil\frac{i-2}{2}\right\rceil&=\sum_{n=3}^\infty\frac{1}{2^n}\sum_{i=3}^n\left\lfloor\frac{i-1}{2}\right\rfloor\\ &=\sum_{n=3}^\infty\frac{1}{2^n}\sum_{i=2}^{n-1}\left\lfloor\frac{i}{2}\right\rfloor &=\sum_{n=3}^\infty\frac{1}{2^n}\left\lfloor\frac{(n-1)^2}{4}\right\rfloor\end{align*} with $n=2m\quad$ then $\displaystyle\quad S_{2m}=\sum_{m=2}^\infty\frac{1}{2^{2m}}\left\lfloor\frac{(2m-1)^2}{4}\right\rfloor=\sum_{m=2}^\infty\frac{m^2-m}{2^{2m}}=\sum_{m=1}^\infty\frac{m^2+m}{2^{2m+2}}$

with $n=2m+1\quad$ then $\displaystyle\quad S_{2m+1}=\sum_{m=1}^\infty\frac{1}{2^{2m+1}}\left\lfloor\frac{(2m)^2}{4}\right\rfloor=\sum_{m=1}^\infty\frac{m^2}{2^{2m+1}}$

So $\displaystyle\quad S=S_{2m}+S_{2m+1}=\sum_{m=1}^\infty\frac{3m^2+m}{4^{m+1}}=\boxed{\frac{2}{3}}$

$\endgroup$
0
$\begingroup$

Start with the generating function for $\displaystyle a_i=\left\lceil \frac{i-2}{2}\right\rceil\; , i\ge 3$

which turns out to be

\begin{align*} G(x) &= \frac{x^3}{1-x-x^2+x^3} \end{align*}

and for the sum of the coefficients, it's

\begin{align*} H(x) &= \frac{1}{1-x}\, G(x) \end{align*}

and the required answer is $\displaystyle H\left(\frac{1}{2}\right)$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.